La simplificación administrativa y su impacto en la balanza comercial peruana 2006-2010. - Córdoba Farromeque, Teresa Eliana (2012)
After the liberalization of the Peruvian foreign trade, our country confronted serious economic crises up to becoming stable and to turn into an exporting country opened for the world. Due to it they proposed changes and new strategies to innovate and to improve our administrative processes, in order to come more near the consumer and to be more competent in the international area. It is so our exterior trade becomes more dynamic and every time we can perceive with major brightness the effects that it brings I obtain the incursion of the Peruvian market in the international one. In this regard, by the present research entitled "Administrative Simplification AND ITS IMPACT ON TRADE BALANCE PERUVIAN 2006-2010", is to analyze the improvement of the management of international trade Peruvian evaluate the relationship between administrative simplification as part of management of international trade and its expansion, and finally measure the degree of importance that has administrative simplification in the flow of the trade balance in the study period. The results obtained in this research could serve to customs policies are consistent with the new strategy of facilitating international trade proposed in international contracts, so these results could be taken into account by economic agents (companies governments and families), so they can make good decisions and timely in their strategic plans. Based on the above, it presents the main conclusions and recommendations of the thesis, hoping that they can contribute to the improvement of the export and importer sector of the Peruvian economy.